2018
DOI: 10.1097/prs.0000000000004460
|View full text |Cite
|
Sign up to set email alerts
|

IDEAL IMPLANT Structured Breast Implants: Core Study Results at 6 Years

Abstract: Background:The structured breast implant uses different technology than saline or silicone gel implants, making it a third type of implant. The U.S. Food and Drug Administration and Health Canada granted approval in November of 2014. This implant is filled with saline but has an internal structure consisting of a series of nested shells that support the upper pole when upright and control fluid movement. It combines certain key features and benefits of saline and silicone gel implants. As with saline, the fill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 4 publications
0
14
0
3
Order By: Relevance
“…Saline implants do not have a natural feel because movement of the saline filler is rapidly displaced with motion. Because the implant shell is unsupported, the upper pole collapses when upright and the shell tends to wrinkle 14 …”
Section: Saline Breast Implantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Saline implants do not have a natural feel because movement of the saline filler is rapidly displaced with motion. Because the implant shell is unsupported, the upper pole collapses when upright and the shell tends to wrinkle 14 …”
Section: Saline Breast Implantsmentioning
confidence: 99%
“…The silicone gel implant has a natural feel because the viscosity of the silicone gel filler mimics the breast tissue. The cross‐linked silicone gel supports the implant shell, so there is less upper pole collapse when upright and less wrinkling compared with the saline implant 14 …”
Section: Silicone Implantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the structured IDEAL IMPLANT is saline-filled, it is a distinctly different type of implant than unstructured single-lumen saline-filled implants or silicone gel-filled implants, making it a third type of breast implant [14].…”
Section: Introductionmentioning
confidence: 99%
“…1). [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] Several studies published about 4 decades ago reported capsular contracture rates in the range of 27-40% after breast augmentation. [24][25][26][27][28][29] This spike in capsular contracture rates was caused by leak-prone thin-shelled second generation implants inserted in the 1970s, which almost always ruptured within a decade of insertion.…”
mentioning
confidence: 99%